Pemikiran Zakiah Daradjat Tentang Pendidikan Anak dalam Keluarga - Mahmudah, Ema; Sauri, Sofyan; Bahruddin, Ending (Ta'dibuna: Jurnal Pendidikan Islam, 2013)
A family constitutes the first and the main educational institution to form a child having an Islamic personality, being obedient to worship God and having a broad knowledge which is useful for this life. Rampaging various moral degradations and akhlak of children and teenagers are indeed started from the misled education in the family. A family education is started from pregnancy to the end of life. Thus, it is needed a deep study toward the concept of children education in the family. The thought of Zakiah Daradjat as the figure of educator and muslim intellectual related to the concept of children education in the family which is become the object of this research, especially in her book entitled Pendidikan Islam dalam Keluarga dan Sekolah. The goals of this research are to (1) Know the Concept of Human Being in Education according to Zakiah Daradjat, (2) Know The Goal of Islamic Education in a Family according to Zakiah Daradjat, (3) Know the Concept of Islamic Education in a Family according to Zakiah Daradjat, (4) Know the Concept of Family as the Media of Education according to Zakiah Daradjat, (5) Know the Effort to Form Children Personality in a Family according to Zakiah Daradjat. This research constitutes a kind of library research, meaning a research using descriptive data and explored from various relevant literatures. As for the primary data are explored from the work of Zakiah Daradjat entitled Pendidikan Anak dalam Keluarga dan Sekolah, and the secondary ones are explored from other Zakiah Daradjat’s books as well as some relevant literatures and supporting the problems discussed in this research. The result of this dissertation denotes that Zakiah Daradjat constitutes a figure having comprehensive point of view and thought related to children education in a family. Children education in a family which is operationally performed by a mother should touch seven dimensions completely and systematically. Zakiah Daradjat offers a concept of religious education in a family by using a psychological approach namely from children moral and conduct. The goal of children education in a family according to Zakiah Daradjat’s thought is to form a child having Islamic personality by the indications having strong iman (faith) and tauhid (unity of God), being obedient to worship God, having a noble character, having a broad knowledge which is useful and having life skill as a foothold to have a role in society. All of these should be applied through education in a family by using love and affection approach, parents’ teaching and exemplary at home as well as a positive environment around the house.